Participation of City Communities in Paying Land and Building Taxes in the Rural and Urban Sectors (PBB-P2) - Riva Ratna Krisnandia; Nopa Pujihastuti; Aussy Mahardika Putri; Hery Nariyah; Sri Wulandari (Jurnal Syntax Transformation, 2024)
Land and Building Tax (PBB) has an important role in supporting the development and administration of local government. However, low community participation can hinder the achievement of the maximum potential of this revenue source. This study aims to analyze the factors that cause the unoptimal participation of urban communities in the payment of Land and Building Tax (PBB) in Kuningan District. This research method uses a qualitative approach with descriptive research type. Data collection techniques were conducted through field studies with interviews, which were supported by data analysis. The research location is in Kuningan Sub-district, Kuningan Regency. The results of this study identified socio-economic, administrative, and psychological factors and found regulatory factors to be the cause of low community participation in PBB payments. This research also provides recommendations regarding efforts that need to be made to optimize the level of urban community participation in PBB payments in Kuningan Sub-district.